Learning Application of English Subject for Children with Intellectual Disability - Lontoh, Olivia I.J.; Tulenan, Virginia; Kaunang, Sumenge T.G. (Universitas Sam Ratulangi, 2019)
Abstract — English is one of the essential subjects in education. English subject is also included in the special needs education, in this case specifically for children with intellectual disability. Children with intellectual disability generally have difficulties in understanding lesson materials. This application is a solution to help the children in SLB YPAC Manado to learn English. This research uses Multimedia Development Life Cycle (MDLC), a software development method which consists of six stages and this application is equipped with lesson materials, along with sub-features such as sound. The purpose of this application development is to create a more compelling and easy-to-use learning media that can help children with intellectual disability to get a better understanding of English. Keywords — Children with Intellectual Disability, English, Learning Application, MDLC.Abstrak — Mata pelajaran bahasa Inggris merupakan mata pelajaran yang sangat diperhitungkan dalam bidang pendidikan. Penerapannya sampai kepada dunia pendidikan anak tunagrahita. Anak tunagrahita memiliki kesulitan dalam memahami materi akademik. Salah satu upaya adalah pembuatan sebuah media pembelajaran interaktif yang memudahkan anak tunagrahita dalam memahami materi. Aplikasi ini merupakan solusi dalam membantu siswa tunagrahita SLB YPAC Manado dalam mempelajari bahasa Inggris. Multimedia Development Life Cycle (MDLC) merupakan metode pengembangan perangkat lunak yang memiliki 6 tahap dan aplikasinya dilengkapi dengan materi pengajaran serta sub fitur berupa suara. Dengan dibuatnya aplikasi ini diharapkan dapat memudahkan anak tunagrahita dalam memahami materi dan proses pembelajaran yang menarik dan mudah digunakan.Kata kunci — Aplikasi Pembelajaran, Bahasa Inggris, MDLC, Tunagrahita.